Are multinationals and governments from emerging economies configuring global value chains in new ways?. Issue 1 (12th March 2019) - Alvstam, Claes; Ivarsson, Inge; Petersen, Bent
Abstract : Purpose: The hallmark of today's global value chains (GVCs), still dominated by multinationals from advanced economies, is a sophisticated international division of labor based on scale economies and prevailing factor endowment differences between countries. However, GVCs led by multinationals from large emerging economies may be configured on the basis of considerations that supplement factor cost efficiencies, namely, those of societal objectives as formulated by political actors in the home country. In this context, the purpose of this paper is to examine the implications of political and socio-economic factors on GVC configuration of multinational firms. Design/methodology/approach: This paper provides an in-depth case study of a leading Chinese car manufacturer, Zhejiang Geely Holding Group (ZGH) and its value-chain configuration, with a special focus on the acquisition of Volvo Car Corporation. Findings: The authors show how ZGH's configuration of its GVC, including that of acquired Volvo Car Corporation, takes place in symbiosis with political actors. The advantages and disadvantages of this symbiosis are highlighted. Research limitations/implications: The study focuses on GVC configuration of one company, ZGH, in one industry, the automotive industry, in one emerging economy. The external validity of the study may therefore be limited. Furthermore, the focus is on the geographical/locational configuration of GVCs and ignores the ownership aspects. Originality/value: The paper provides novel empirical evidence to better understand GVC configuration of multinational firms from emerging economies.